HAK SEWA TANAH UNTUK BANGUNAN OLEH WARGA NEGARA ASING (WNA) SEBAGAI ALTERNATIF PENGUASAAN HAK ATAS TANAH DI INDONESIA - Carona, Nina; Rifai, Anis; Shebubakar, Arina Novizas (Faculty of Law, Universitas Pasundan, 2024)
Land plays a crucial role in the life of Indonesian society and economy, particularly in tourist destinations like Bali. The establishment of businesses by foreign nationals in Bali, especially in the region of Badung Regency, has raised concerns regarding regulations governing land ownership. The Land Law Number 5 of 1960 concerning Agrarian Affairs and Government Regulation Number 46 of 1996 strictly regulate land ownership by both Indonesian citizens (WNI) and foreign nationals (WNA), particularly in terms of land lease for building purposes. However, there remain uncertainties concerning the understanding of land lease agreements for buildings, including time limitations, lease extension, and the status of buildings constructed on leased land after the lease agreement expires. This study employs a normative juridical research method with a legislative approach to provide a better understanding of land ownership for WNAs in business development in Bali and Indonesia as a whole. Keywords: Land Ownership, Land Lease for Building Purposes, Land Lease Agreements, Ease Agreements.